Predictors of impaired endothelial function in obstructive sleep apnea syndrome - Šiarnik, Pavel; Čarnická, Zuzana; Krížová, Lucia; Wágnerová, Helena; Šutovský, Stanislav; Klobučníková, Katarína; Kollár, Branislav; Turčáni, Peter; Sykora, Marek (Neuroendocrinology letters, 2014)
OBJECTIVES: Obstructive sleep apnea syndrome (OSA) is associated with increased cardiovascular morbidity and mortality. Endothelial dysfunction (ED), accelerated atherosclerosis and autonomic dysfunction might be the key players responsible for development of vascular diseases in patients with OSA. In a population with suspected OSA and low burden of cardiovascular risk factors, we therefore aimed to investigate the association between potential cardiovascular risk factors including OSA-specific indices, ED and autonomic activity. - METHODS: ED was investigated using reperfusion hyperaemia index (RHI). OSA was assessed using standard polysomnography, autonomic activity was assessed using baroreflex sensitivity (BRS). - RESULTS: We enrolled 31 patients (42.1±11.7 years) with OSA. Significant inverse correlation was found between RHI and apnea-hypopnea index (AHI) (r=-0.550, p=0.001) and between RHI desaturation index (r=-0.533, p=0.002). Positive correlation was found between RHI and minimal nocturnal oxygen saturation (r=0.394, p=0.028). In a multiple regression model AHI was the only significant variable to predict RHI (β=-0.522, p=0.003). We found no correlation between RHI and BRS. RHI in the population with severe OSA (AHI above 30) was significantly lower than RHI in the rest of the population (p=0.012). - CONCLUSION: AHI was the only significant independent predictor of impaired endothelial function as expressed by RHI. RHI showed no association with BRS in patients with OSA.
Gesehen am 28.09.2020